'Disable them all': SENCO and LSA conceptualisations of inclusion in physical education. Issue 2 (12th February 2018) - Maher, Anthony John
ABSTRACT: There is a propensity for academics and policy makers in Britain to use the terms integration and inclusion synonymously, possibly resulting in diverse interpretations of the inclusion principles laid out in the new National Curriculum. Much of the research available relating to conceptualisations of inclusion in physical education (PE) is from the perspective of teachers. Moreover, PE as a relatively unique learning environment is often neglected in much of the research that does analyse educational inclusion. In this paper, the key theoretical tools of cultural studies, in particular the concept of cultural hegemony, are used to analyse how special educational needs coordinators (SENCOs) and learning support assistants (LSAs) conceptualise inclusion in mainstream secondary school PE in Britain. Semi-structured, individual interviews explored SENCO ( n = 12) and LSA ( n = 12) educational ideologies and experiences of SEN and inclusion in PE. Open, axial and selective coding was undertaken to systematically analyse (textual) data. The research found that most conceptualisations reflected a social ideology because they focused on how educational arrangements can be made to ensure that pupils with SEN have comparable learning experiences to their age peers. Emphasis was placed on the power and influence of PE teachers, and the importance of identifying the specific needs and capabilities of pupils with SEN, as ways of ensuring that an inclusive culture can develop and is maintained in PE. The paper concludes by arguing that PE teachers and LSAs need access to PE-specific and up-to-date guidance and learning targets so that they can use the influence they have over the norms and values of PE to cultivate an inclusive culture in that subject.